The prophylactic effects of BIFICO on the antibiotic-induced gut dysbiosis and gut microbiota - Wu, Jiannong (Gut Pathog, 2020)
BACKGROUND: The aim of this study is to evaluate the prophylactic effects of probiotic mixture BIFICO on antibiotic-induced gut dysbiosis (AIGD) and the influence on the change of the gut microbiota. METHODS: We conducted a prospective, randomized, controlled study and divided 196 patients who required intravenous beta-lactam antibiotics into three groups: a control group (no probiotics), a regular group (840 mg of BIFICO), and a double-dosage group (1680 mg of BIFICO). The symptoms of antibiotic-related diarrhea, bloating and abdominal pain and the incidence of AIGD were evaluated 7 days and 8–14 days after antibiotic use, with 10 patients in each group. 16S rDNA sequencing was performed to detect changes of the gut microbiota. RESULTS: Within 7 days of the initiation of antibiotic treatment, the incidences of AIGD in the control group, regular group (840 mg of BIFICO), and double-dosage group (1680 mg of BIFICO) were 21.88%, 14.93%, and 6.15% respectively. On days of 8–14th, the incidences of AIGD in the control group, regular group, and double-dosage group were 25%, 14.93%, and 4.62%, respectively. The incidence of AIGD in the double-dosage group within 7 days and 14 days were both significantly lower than that in relevant control group (P < 0.05). On day 14, the incidence of AIGD in the double-dosage group was lower than that in the regular group (P < 0.05). The number of operational taxonomic units (OTUs) in the control group after antibiotic treatment was significantly reduced compared to that prior to treatment, while those of the regular and double-dosage groups were stable. The species abundance, especially Parabacteroides, Phascolarctobacterium and Roseburia, of the double-dosage group was greater than that of the regular group and the control group. CONCLUSIONS: BIFICO may reduce the occurrence of AIGD in a dose-dependent manner and can stabilize the gut microbiota balance.